Analisis Manajemen Risiko pada Usaha Bengkel - Geagri, Rifa Ghaza (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Auto repair shops play a crucial role in supporting community mobility and the local economy. However, these businesses often face various risks that can hinder growth and business continuity. These risks include fluctuations in spare parts prices, financial challenges, limitations in human resources, and operational and marketing difficulties. Without effective risk management, auto repair shops risk experiencing a decline in profitability and competitiveness. Therefore, risk analysis is needed to help auto repair shops identify, assess, and manage potential risks to maintain business stability and optimize growth in the future. The SGH Auto Repair Shop was established in 2024 in Garut, with the primary goal of meeting the needs for vehicle repair and maintenance. This study aims to identify and analyze the main risks faced by SGH Auto Repair Shop in terms of spare parts, finance, human resources, operations, and marketing, and to provide mitigation recommendations to minimize these risks. Data was collected through interviews with the business owner and analyzed descriptively using a SWOT approach. The study results indicate that spare parts risks include price increases and inconsistent quality, while financial risks stem from cash flow instability. Operationally, the auto repair shop faces technical issues and lacks standardized procedures. In conclusion, SGH Auto Repair Shop needs to improve its risk management through supplier diversification, better financial recording, and optimized competitive strategy. Effective risk management is expected to help maintain the continuity and enhance the competitiveness of SGH Auto Repair Shop.